2023
DOI: 10.1038/s41598-023-28387-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen metabolism in the proliferation of Korean pine embryogenic callus cells promoted by exogenous GSH

Abstract: Exogenous glutathione (GSH) promotes the proliferation of embryogenic callus (EC) cells in Korean pine in the course of somatic embryogenesis, and reactive oxygen species (ROS) may play an important role in regulating the proliferation of EC cells by exogenous GSH. However, the concrete metabolic response of ROS is unclear. In this study, two cell lines of Korean pine with high proliferative potential 001#-001 (F, Fast proliferative potential cell line is abbreviated as F) and low proliferative potential 001#-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a study of Korean pine embryogenic callus, GSH was observed to promote the growth of embryogenic callus and maintain higher embryogenicity during the proliferation stage [11]. In a study of Araucaria angustifolia, it was found that the addition of GSH reduced the production of NO in cells and improved the quantity, quality, and development of early somatic embryos [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Korean pine embryogenic callus, GSH was observed to promote the growth of embryogenic callus and maintain higher embryogenicity during the proliferation stage [11]. In a study of Araucaria angustifolia, it was found that the addition of GSH reduced the production of NO in cells and improved the quantity, quality, and development of early somatic embryos [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been discovered that the sterol hormone brassinolide (BL) has the ability to loosen the cell wall, increase the volume of the cell, and promote cell division and cell growth [9]. The presence of melatonin (Mel) and salicylic acid (SA) can modify the activity of antioxidant enzymes in plants [10], while glutathione (GSH) is known to maintain embryogenic callus at the proliferation stage [11]. Ascorbic acid (AsA) has been found to promote somatic embryogenesis in Fraxinus mandshurica [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the embryogenic callus of Pyrus communis was high in solubility and protein, but low in starch (Ameri et al 2020). Peng et al (Peng et al 2022;Gao et al 2023) suggested that high starch content in the embryogenic callus was the basis for successful somatic embryogenesis. In this study,the contents of soluble sugar, protein, and starch in the Y7-20 cell line with higher embryonicity (better ESM structure development) were significantly higher than those in the cell lines with lower embryonicity.…”
Section: Effects Of Psk On the Contents Of Stored Substances Of P Mas...mentioning
confidence: 99%